THE DEVELOPMENT OF LEADERSHIP SKILLS IN YOUNG PEOPLE: A PSYCHOANALYTICAL ANALYSIS OF UNCONSCIOUS DYNAMICS AND CONTEMPORARY CHALLENGES - Freitas, Fernanda Machado (Seven Editora, 2025)
The article proposes an integrative analysis of the development of youth leadership from a psychoanalytical perspective, considering the specific challenges faced by the new generations. Faced with a global scenario marked by intense connectivity, technological transformations and social instability, the importance of training leaders with emotional maturity, ethics and psychological resilience is highlighted. Psychoanalysis is presented as a valuable tool for understanding unconscious processes, identity conflicts and the formation of the self, which directly influence the exercise of leadership.The study aims to investigate the psychoanalytical bases related to leadership development, identify psychic competencies relevant to this process, analyze the difficulties faced by young people and explore intervention strategies. By considering the impact of social networks and technologies on the subjective and relational constitution of individuals, the article offers theoretical and practical contributions for professionals involved in training young leaders.DOI: https://doi.org/10.56238/sevened2025.026-008